Vehicle routing planning for logistics - Wei-You Liu; Shan-Ping Chuang (2010 Sixth International Conference on Networked Computing and Advanced Information Management, 2010)
When planning transport in the logistics industry, the main issue is to enhance efficiency and save total transportation costs. Using special systems and transport process will improve the value of services. Previous papers had focused on the external service network of trucks; only few discuss the internal network within one company. The inter-service area of cargo transportation and logistics industry mainly depends on long-haul transport, but in actual operation, there is the problem of vacant car on return trips. Thus, improving the internal operation in existing line to lower vacant cars will cut down costs, thereby improving the company's revenue. The main motivation for this study is to find the best cost-effective way of transportation under different carry volume using complementary and sourcing practices.